Al confine tra paura e desiderio Politiche della memoria e soggettività di richiedenti asilo in Italia - Giudici, Daniela (FrancoAngeli, 2021)
This book is an ethnographic study of reception centers and support services for asylum seekers in Bologna, Italy. Starting from an anthropological perspective, it explores the intersubjective construction of a set of legal categories (i.e., asylum seeker or refugee), to show their implementation and transformation in the everyday life of individuals and institutions. At the same time, this research sheds light on the inherent complexity of asylum seekers' life experiences, which are embedded in a multiplicity of dimensions - political, affective, historical - often overlooked by contemporary asylum systems.